Effect of Vibrating Footing on a Nearby Static – Load Footing - Saif Khalil Ibrahim; Waad A. Zakaria (Civil Engineering Journal, 2019)
This paper presents an experimental study on the dynamic response of square footings under effect of dynamic load comes from adjacent footing called the (source of vibration (which is excited by a known vibration source placed on the top of it, the objective is to study the effect of dynamic motion of the source of vibration on a nearby footing, called second footing, both footings rest on collapsible soil (gypseouse soil) with gypseouse content (60%). The study is performed through wide experimental program in dry and soaked condition. The first footing (source vibration) and the second footing have dimensions (80 80 40), (100 100 40) mm respectively and are manufactured from steel, then the two footings placed centrally over soil after prepared it in layers’ form in steel container with (1000 500 500) mm. The first footing exposed to vertical harmonic loading by using a rotating mass type mechanical oscillator to gives a similar effect of the dynamic loads, the second footing loaded with static weight only, under the dynamic excitation. The tests are conducted under dynamic response for three frequencies (10, 20, 30) Hz, the movement (displacement amplitude, velocity, and acceleration) of the second footing studied by varying spacing between the footings. The results showed that the amplitude of displacement, velocity, and acceleration for the second footing decreases when the spacing between footing increase. In addition, the value of these parameters at dry state is greater than its value at soaked state.